Inicial development of Tectona grandis l.f under nutricional restriction - Nascimento, Diego Arcanjo do [UNESP]; Filho, Otávio Peres; Favare, Lilian Guimarães; Souza, Marcelo Dias; Dos Santos, Alexandre; Silva Junior, Josamar Gomes (Universidade Federal do Paraná, 2020)
In the process of seedling production plant nutrition can improve the quality. Among the forest species, the teak stands out for the resistant wood and its rusticity. The knowledge of the nutritional needs of teak seedlings favors its development with reflex in the field production. The experiment was conducted in a greenhouse with seedlings planted in 3 liter pots, as substrate we used underground soil. The treatments were divided into: control, complete solution; omission of N, omission of P, omission of K, omission of Ca, omission of Mg, omission of Si. To evaluate the effects of treatments on plants, we measured total height and stem diameter, with six biweekly readings. The observations were submitted to analysis of variance and the means were compared by Tukey test at 5% probability. Subsequently, linear regression models were adjusted, containing as independent variable: development time; and variable dependent height and diameter of the collection per treatment. There was no significant difference between treatments in the variable total height of plants, only in stem diameter where the complete treatment had the highest mean values. In the first months of development of teak, it was possible to observe a sufficient performance in the evaluated variables, however, fertilization should be carried out for a satisfactory production, mainly containing the macronutrients N, P, K.
Keywords: Forestry; Mineral fertilization; Teak